THE EXPANSION OF THE PERFORMANCE OF THE JUDICIAL POWER: LIMITS AND PARAMETERS FOR A JUDICIALIZATION IN THE LIGHT OF THE EFFICIENCY PRINCIPLE - Neder dos Santos, Erika; Xavier Laguardia, Nathalia (Revista Gênero e Interdisciplinaridade, 2022)
The Constitution of the Federative Republic of Brazil, with a lot of wisdom, brought several fundamental rights in your text. The search for your implementation, therefore, should be the driving spring of State action. However, the State does not have budget necessary to effect compliance with all fundamental rights described in your text, and many times do not have political will for the achievement of the constitutional dictates. Because of this, the Government must make choices designed to confer greater effectiveness for devices of the Constitutional Charter. Must have as purpose to pursue public purposes of the execution of rights to a larger number of individuals, giving priority to the constitutional principle of efficiency. Still, there will be situations of inefficiency and even State failure. In this case, the judiciary will have to decide on the effective allocation of certain rights through the phenomenon of judicialization, IE, the judiciary has been asked to check effectiveness of the provisions of the Constitution of the The Federative Republic of Brazil, so that this new arrangement between the three powers should be examined on the light of the principle of efficiency. The present study aims to reconcile the growing role of the judiciary, its limits and parameters, with the analysis of the State efficiency in effective enforcement of fundamental rights listed in CRFB. This growing number of lawsuits is able to make the State more efficient in pursuit of your purpose? Or just being an obstacle to the pursuit of the public interest?